A possible solution to model nonlinearity in elimination and distributional clearances with α2-adrenergic receptor agonists: Example of the intravenous detomidine and methadone combination in sedated horses - Gozalo-Marcilla, Miguel; Moreira da Silva, Rodrigo; Pacca Loureiro Luna, Stelio [UNESP]; Rodrigues de Oliveira, Alice [UNESP]; Werneck Fonseca, Mariana [UNESP]; Peporine Lopes, Norberto; Taylor, Polly M.; Pelligand, Ludovic (Wiley, 2019)
The alpha(α)2-agonist detomidine is used for equine sedation with opioids such as methadone. We retrieved the data from two randomized, crossover studies where detomidine and methadone were given intravenously alone or combined as boli (STUDY 1) (Gozalo-Marcilla et al., 2017, Veterinary Anaesthesia and Analgesia, 2017, 44, 1116) or as 2-hr constant rate infusions (STUDY 2) (Gozalo-Marcilla et al., 2019, Equine Veterinary Journal, 51, 530). Plasma drug concentrations were measured with a validated tandem Mass Spectrometry assay. We used nonlinear mixed effect modelling and took pharmacokinetic (PK) data from both studies to fit simultaneously both drugs and explore their nonlinear kinetics. Two significant improvements over the classical mammillary two-compartment model were identified. First, the inclusion of an effect of detomidine plasma concentration on the elimination clearances (Cls) of both drugs improved the fit of detomidine (Objective Function Value [OFV]: −160) and methadone (OFV: −132) submodels. Second, a detomidine concentration-dependent reduction of distributional Cls of each drug further improved detomidine (OFV: −60) and methadone (OFV: −52) submodel fits. Using the PK data from both studies (a) helped exploring hypotheses on the nonlinearity of the elimination and distributional Cls and (b) allowed inclusion of dynamic effects of detomidine plasma concentration in the model which are compatible with the pharmacology of detomidine (vasoconstriction and reduction in cardiac output).
Keywords: alpha(α)2-adrenergic receptor agonist; alpha-2 agonist; cardiac output; equine; nonlinear mixed effect modelling; opioid; pharmacokinetics; population pharmacokinetics